Fabrication and Effect of Strontium-Substituted Calcium Silicate/Silk Fibroin on Bone Regeneration In Vitro and In Vivo - Zhou, Yuning; Hu, Yue; Uemura, Mamoru; Xia, Lunguo; Yu, Xingge; Xu, Yuanjin (Frontiers in Bioengineering and Biotechnology, 2022)
Achieving rapid osteogenesis and angiogenesis was the key factor for bone regeneration. In the present study, the strontium-substituted calcium silicate (SrCS)/silk fibroin (SF) composite materials have been constructed, via combining the different functional components ratio of SrCS (12.5 wt%, 25 wt%) and SF. Then, the effects of SrCS/SF materials on proliferation, osteogenic differentiation and angiogenic factor secretion of rat bone marrow-derived mesenchymal stromal cells (rBMSCs) were first evaluated in vitro. Moreover, the in vivo effect of osteogenesis was evaluated in a critical sized rat calvarial defect model. In vitro studies showed that SrCS/SF significantly enhanced the cell proliferation, alkaline phosphatase (ALP) activity and the expression of osteogenic and angiogenic factors of rBMSCs as compared with the SF and CS/SF, and the optimum proportion ratio was 25 wt%. Besides, the results also showed that CS/SF achieved enhanced effects on rBMSCs as compared with SF. The in vivo results showed that 25 wt% SrCS/SF could obviously promote new bone formation than SF and CS/SF. The present study revealed that SrCS could significantly promote the osteogenic and angiogenic activities of SF, and SrCS/SF might be a good scaffold material for bone regeneration.